A high-strength vacuum brazed TC4/316L joint with a Ti–Zr-based amorphous ribbon as the filler metal. (May 2021) - Cao, Xu; Dong, Kewei; Zhu, Rui; Wang, Qingyu; Kong, Jian
Abstract: The melting point of most of the Ti-based amorphous alloys is higher than the transformation temperature of titanium alloys, bringing a detrimental effect to the joint. In this work, a multicomponent Ti35 Zr25 Be40-x Cox (x = 2, 4, 6, 8, 10) amorphous ribbon with a minimum melting point of 765 °C was designed through tunning the content of Co and applied as the filler metal to vacuum braze dissimilar materials TC4 and 316L steel. In order to investigate the influence of brazing temperature and holding time on the microstructure evolution and mechanical properties, the brazing was conducted at different temperatures and holding for different time. Experimental results show that the content of dendritic phases in the joint increased with increasing the brazing temperature and holding time and due to the interaction of multiple elements, fine phases TiCo, TiFe formed and uniformly dispersed in the gap area and in the interdendritic regions, strengthening the joint. Mechanical properties of the joint were evaluated by shearing test and microhardness and it was found that the shear strength firstly increased and then decreased as the temperature increased. A maximum shear strength of 225 MPa was obtained when brazed at 830 °C for 15min. Highlights: A Ti35 Zr25 Be30 Co10 amorphous filler was designed by tunning the element Co. High-strength joining of TC4 and 316L was obtained below the α to β transformation point. The formation of fine phases in the inter-dendritic region greatly strengthened the joint.